Focusing on A New Generation in Japan '94 : Statements from 10 Galleries. (Tokyo : Tokyo Contemporary Art Gallery Meeting, 1994)
Higuchi, Yasuki ; Nakayama, Daisuke ; Takatsu, Mie ; Tokunaga, Masayuki ; Kitazawa, Takayuki ; Kato, Gaku ; Suzuki, Takahiro ; Nakazawa, Ken ; Yonekawa, Harumi ; Takahama, Toshiya
Focusing on A New Generation in Japan '94 : Statements from 10 Galleries (Gallery 21+YO ; Gallery K. ; Gallery Kobayashi ; Kaneko Art Gallery ; AI Gallery ; Nabis Gallery ; Gallery GEN ; Gallery Yamaguchi ; Gallery Lunami ; Gallery Natsuka), Tokyo, 1994
English-Japanese
kunstcatalogus
Keywords: Japan